ERS/ESICM/ESCMID/ALAT guidelines for the management of severe community-acquired pneumonia. Issue 4 (3rd April 2023) - Martin-Loeches, Ignacio; Torres, Antoni; Nagavci, Blin; Aliberti, Stefano; Antonelli, Massimo; Bassetti, Matteo; Bos, Lieuwe; Chalmers, James D.; Derde, Lennie; de Waele, Jan; Garnacho-Montero, Jose; Kollef, Marin; et al.
Background: Severe community-acquired pneumonia (sCAP) is associated with high morbidity and mortality, and while European and non-European guidelines are available for community-acquired pneumonia, there are no specific guidelines for sCAP. Materials and methodology: The European Respiratory Society (ERS), European Society of Intensive Care Medicine (ESICM), European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and Latin American Thoracic Association (ALAT) launched a task force to develop the first international guidelines for sCAP. The panel comprised a total of 18 European and four non-European experts, as well as two methodologists. Eight clinical questions for sCAP diagnosis and treatment were chosen to be addressed. Systematic literature searches were performed in several databases. Meta-analyses were performed for evidence synthesis, whenever possible. The quality of evidence was assessed with GRADE (Grading of Recommendations, Assessment, Development and Evaluation). Evidence to Decision frameworks were used to decide on the direction and strength of recommendations. Results: Recommendations issued were related to diagnosis, antibiotics, organ support, biomarkers and co-adjuvant therapy. After considering the confidence in effect estimates, the importance of outcomes studied, desirable and undesirable consequences of treatment, cost, feasibility, acceptability of the intervention and implications to health equity, recommendations were made for or against specific treatment interventions. Conclusions: In these international guidelines, ERS, ESICM, ESCMID and ALAT provide evidence-based clinical practice recommendations for diagnosis, empirical treatment and antibiotic therapy for sCAP, following the GRADE approach. Furthermore, current knowledge gaps have been highlighted and recommendations for future research have been made. Severe community-acquired pneumonia (sCAP) is associated with high morbidity and mortality, and while European and non-European guidelines are available for CAP, there are no specific guidelines for sCAP http://bit.ly/3DpnwA3